Introduction: Art’s Dialectical Role in Urban Social Struggles - Tijen Tunali (User Experience & Urban Creativity)
Much has been written about how cities are central to the spatial development of neoliberalism, where the macro-politics of globalizing economies make and unmake landscapes and architectures within which the micro-politics of many millions of people’s day-to-day existences are lived out (Lefebvre 1968, 1974, 2000, 2003; Harvey 2006, 2012; Sennett 1994; Tonkiss 2005). As a response to this urban experience, identified as deeply segregated urban landscapes and social inequality, a growing urban resistance has also become visible features of urban life (Purcell 2008).